2020
DOI: 10.2516/ogst/2020033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on thermal, rheological and filtration control characteristics of drilling fluids: effect of nanoadditives

Abstract: Cooling the drill bit is one of the major functions of drilling fluids, especially in high temperature deep drilling operations. Designing stable drilling fluids with proper thermal properties is a great challenge. Identifying appropriate additives for the drilling fluid can mitigate drill-bit erosion or deformation caused by induced thermal stress. The unique advantages of nanoparticles may enhance thermal characteristics of drilling fluids. The impacts of nanoparticles on the specific heat capacity, thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…where k e (t) is the equivalent filter cake permeability, mD; k 1 is the real situation with time-dependent filter cake permeability, mD; w o is the constant filter cake thickness, m; w(t) is the real situation with time-dependent filter cake thickness, m; and r w is the filter cake inner radius, m. During drilling, many factors such as drill-string rotational speed, annulus velocity, drilling fluid type, solid particle size, formation temperature, formation pressure, and formation permeability, can influence the time-dependent properties of the filter cake (Jaffal et al, 2018;Ma et al, 2020;Ribeiro et al, 2017;Veisi et al, 2020;Yao et al, 2014). Some experimental and mathematical models have been conducted to study the filter cake growth process (Fisher et al, 2000;Hashemzadeh and Hajidavalloo, 2016;Jaffal et al, 2017;Ma et al, 2020;Rabbani and Salehi, 2017), and their results showed that both the thickness and permeability of filter cake obey the exponential changing modes.…”
Section: Equivalent Filter Cake Permeabilitymentioning
confidence: 99%
“…where k e (t) is the equivalent filter cake permeability, mD; k 1 is the real situation with time-dependent filter cake permeability, mD; w o is the constant filter cake thickness, m; w(t) is the real situation with time-dependent filter cake thickness, m; and r w is the filter cake inner radius, m. During drilling, many factors such as drill-string rotational speed, annulus velocity, drilling fluid type, solid particle size, formation temperature, formation pressure, and formation permeability, can influence the time-dependent properties of the filter cake (Jaffal et al, 2018;Ma et al, 2020;Ribeiro et al, 2017;Veisi et al, 2020;Yao et al, 2014). Some experimental and mathematical models have been conducted to study the filter cake growth process (Fisher et al, 2000;Hashemzadeh and Hajidavalloo, 2016;Jaffal et al, 2017;Ma et al, 2020;Rabbani and Salehi, 2017), and their results showed that both the thickness and permeability of filter cake obey the exponential changing modes.…”
Section: Equivalent Filter Cake Permeabilitymentioning
confidence: 99%
“…Therefore, researchers propose to use a combination of synergistic agents and corrosion inhibitors to enhance the corrosion efficiency of corrosion inhibitors through synergistic corrosion inhibition [18]. Nanomaterials are an emerging synergistic additive that, due to their large specific surface area, porous structure, and thermal stability, have been applied in fields such as enhanced oil recovery, improved fracturing fluid performance, and anti-corrosion coatings in the oil and gas industry [19][20][21][22]. Research has shown that adding nanoparticles to VES-based fluids can change the shape of micelles from spherical to vermicular, effectively improving the temperature resistance and rheological properties of VES-based fluids [23].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical incompatibility between injected water and formation brine 1 3 results in mineral scale formation, that is one of the serious problems in oil fields. In addition to the incompatible ionic composition of injection water, inorganic scales are formed due to brine supersaturation with changes in temperature, pressure, and pH value (Farrokhrouz et al 2020;Nikoo et al 2020;Veisi et al 2020;.…”
Section: Introductionmentioning
confidence: 99%